2016
DOI: 10.1016/j.rbmo.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of ovulation induction with metformin for PCOS; what is the best available evidence?

Abstract: The potential reproductive benefits of metformin, a drug endowed with the capacity to ameliorate insulin resistance in polycystic ovary syndrome (PCOS), has garnered much interest over the past 2 decades. In this review, randomized-controlled trials (RCT) and meta-analyses of RCT comparing metformin are critically appraised and summarized. PubMed and CENTRAL databases were consulted. Evidence is insufficient to favour the use of metformin or metformin plus clomiphene citrate instead of clomiphene citrate for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 45 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…Metformin therapy in pregnant women with PCOS has been associated with a significant reduction in the rate of early pregnancy loss [Al-Biate 2015] and improves the pregnancy rate in in vitro fertilization repeaters without PCOS [Jinno et al 2010]. The beneficial effects of metformin therapy could increase the clinical pregnancy rates and reduce the IR in women with PCOS [Abu Hashim 2016]. Collectively, our study indicated that prescription of metformin prior to the pregnancy could not only increase insulin sensitivity and decrease the HOMA-IR score but also improve lymphocyte population aberration, which indicated that IR, cellular Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin therapy in pregnant women with PCOS has been associated with a significant reduction in the rate of early pregnancy loss [Al-Biate 2015] and improves the pregnancy rate in in vitro fertilization repeaters without PCOS [Jinno et al 2010]. The beneficial effects of metformin therapy could increase the clinical pregnancy rates and reduce the IR in women with PCOS [Abu Hashim 2016]. Collectively, our study indicated that prescription of metformin prior to the pregnancy could not only increase insulin sensitivity and decrease the HOMA-IR score but also improve lymphocyte population aberration, which indicated that IR, cellular Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence was of low quality and findings should be interpreted with cautions especially in CCR-PCOS patients. In addition, there was either no difference or insufficient evidence for the comparisons of metformin with CC, placebo and other therapies in PCOS patients 4345 .…”
Section: Discussionmentioning
confidence: 99%
“…As per the literature, the effectiveness of metformin has emerged as a subject of great interest in the 21st century. Hashim et al [ 19 ] reviewed the CENTRAL and PubMed database for evaluating the reproductive benefits of this drug. The assessment of presenting randomized controlled trials (RCTs) and reports of meta-analysis indicated that the empirical evidence is not sufficient enough to indicate any association between the ability to conceive and the administration of metformin among patients of PCOS [ 19 - 20 ].…”
Section: Discussionmentioning
confidence: 99%